Regional Trade Blocs, Location Advantage And Enterprise Competitiveness In The Global Economy - Ogbor, John Oghenechuko; Eromafuru, Edward G. (Archives of Business Research, 2018)
This paper examines the competitiveness of enterprises located in the Sub-Saharan region in the context of the relationship between regional trade blocs, location advantages and the competitiveness of the enterprises in the global economy. First, we examine the concept of regional trade blocs in the context enterprise competition in the global economy. Second, we examine the drivers of enterprise competitiveness in regional trade blocs and their location advantages. Third, we examine the historical and economic context of regionalization of trade and economic activities including the associated location advantages. Fourth, we examine regional trade blocs in the context of the experience of sub-Saharan Africa. Fifth, we examine the experience of sub-Saharan Africa as it relates to the location advantages associated with it. Specifically, the relationship between common political ideology and praxis, geographically closeness, common socio-cultural experience, common historical experience, infrastructure, clusters and enterprise competitiveness are examined. Research questions are phrased/constructed around the above five themes. Method of research is a “thick description” of the literature on the above subject matter. We also employ a critical discursive approach in interpreting what has been written in these areas in order to explore the gap in the knowledge concerning trade regionalization, location advantage and enterprise competitiveness in the context of Sub-Sahara African economy. Finally, recommendations are offered in terms of how African governments and policy-makers can provide an enabling environment, capable of turning the Sub-Saharan region to a regional location advantage for enterprise competitiveness.